PENDAMPINGAN PEMBUATAN MEDIA MANIPULATIF PRE-SERVICE TEACHERS UNTUK PEMBELAJARAN YANG BERMAKNA BAGI SISWA - Hariyani, Sri; Murniasih, Tatik Retno; Zayyadi, Moh; Sumaji, Sumaji (FKIP Universitas Wisnuwardhana, 2023)
Abstract: The fact that teaching mathematics studies show that some students are less able to learn mathematical concepts. The use of manipulative learning media is considered to facilitate students in learning. Universities as determinants of educated graduates accommodate the achievement of graduates who have the ability according to the formulation in the IQF qualification level. The Unikama Mathematics Education Study Program develops skills in making learning media through assistance to pre-service teachers. The problems faced by pre-service teachers include the need for skills to design learning media that are fun and meaningful for students. Based on the problems of the pre-service teachers, the service provider provides a solution in the form of assistance in designing meaningful learning media for students. The learning media offered is manipulative. Manipulative learning media can improve students' understanding of mathematical concepts. Evaluation of the assistance in making manipulative media by pre-service teachers is carried out through class presentations. Each pre-service teacher explained the materials and tools used and how to make manipulative media. Pre-service teachers also convey how to use it. Key Words: manipulative media; accompaniment; pre-service teachers